How Social Media Platforms Manipulate Kidinfluencers? Analysing the Adoption of Deceptive Design Patterns by Big Techs - Albuquerque, Nathalia Freire; Valença, George Augusto; Falcão, Taciana Pontual (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2023: Anais do XXII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2023)
The term kidinfluencer denotes children who produce entertaining content for social media platforms such as TikTok and Instagram. These young artists frequently publish videos or pictures that highlight their skills, pastimes or general activities in their daily routines, which draws a sizable audience. This can result in business collaborations with platform partners, providing children and caregivers with several options for income. Despite the success and fame of a few kidinfluencers, their use of social media has also sparked worries about their privacy, safety, and potential exploitation. This article explores this phenomenon from the perspective of risks brought by social media platforms, which treat children as relevant content creators but neglect their well-being and autonomy online. By mapping previous studies on the topic, we investigate the scenario of young influencers, using the notion of deceptive design patterns as a lens of analysis of platform manipulation of children’s decisions and interests. To address the identified problems caused by these patterns, we present a set of prototypes as suggestions for changing platforms’ features in order to safeguard children’s rights and best interests online.